Wacana Saintifik Hadis dalam Konstruksi Kesahihan Hadis: Kajian Kritis Terhadap Pemikiran Mohamed Zafzaf dan Syuhudi Ismail - Misbahuddin Asaad, (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2022)
This study aims to present hadith research under the normal scientific approach for hadith research, also known as scientific hadith. The scientific discourse of hadith in the construction of hadith validity according to the understanding of Muhammad el-Zafzaf is a procedural pattern of process sequences regarding the ulum of hadith or hadith methodology into scientific approaches and methods, in conducting criticism of hadith based on scientific procedural or so-called scientific hadith. Thus, the process of filtering hadith hadith through the takhrj technique, classifying themes, constructing schemes (sanad i'tibr), and selecting a crucial study path for sanad with the al-ad wa al-ahammul method is the primary process of scientific research in hadith. And criticism of the release of isnad and the content, the identification of the system of hadith validity, and the starting point for distinguishing hadith when deciding hadith procedurally. As well as the adala-an and dhbit-sanad of the hadith become a sub-system for assessing the authenticity of the hadith, after discovering the connection of the sanad (ittishl sanad), and the matan avoids anomalies (sydz) and oddities (illat). Keywords: Mohamed Zafzaf; Scientific Hadith; The Construction of Hadith Validity;